2014
DOI: 10.1136/tobaccocontrol-2014-051742
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the 2009/2010 enhancement of cigarette health warning labels in Uruguay: longitudinal findings from the International Tobacco Control (ITC) Uruguay Survey

Abstract: Background FCTC Article 11 Guidelines recommend that health warning labels (HWLs) should occupy at least 50% of the package, but the tobacco industry claims that increasing the size would not lead to further benefits. This article reports the first population study to examine the impact of increasing HWL size above 50%. We tested the hypothesis that the 2009/2010 enhancement of the HWLs in Uruguay would be associated with higher levels of effectiveness. Methods Data were drawn from a cohort of adult smokers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…The remaining participants who had smoked waterpipe at least once at some point in their lives, even one or two puffs, were classified as ever users. To assess responses to each health warning, participant were asked the question “to what extent do the following health warning labels motivate you to think about stopping or reducing your hookah smoking” (Chang et al 2011; Gravely et al 2014). Participants could choose one of the following responses: ‘not at all’, ‘somewhat’, and ‘very much’.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining participants who had smoked waterpipe at least once at some point in their lives, even one or two puffs, were classified as ever users. To assess responses to each health warning, participant were asked the question “to what extent do the following health warning labels motivate you to think about stopping or reducing your hookah smoking” (Chang et al 2011; Gravely et al 2014). Participants could choose one of the following responses: ‘not at all’, ‘somewhat’, and ‘very much’.…”
Section: Methodsmentioning
confidence: 99%
“…Those who perceive a lower risk from smoking are more inclined to smoke and less likely to stop smoking . Recent studies have found that the same association holds for vaping with those who perceive a lower risk from using a VD more likely to engage in vaping compared to those who perceive a higher risk relative to smoking cigarettes . Also, where one lives might impact beliefs about the relative dangers of vaping.…”
Section: Introductionmentioning
confidence: 99%
“…6 Health warnings constitute a powerful intervention for increasing knowledge about the specific harms of tobacco use 7 and for increasing thoughts and motivations to quit smoking among smokers in many countries including Thailand, Malaysia, Uruguay, Mauritius, Mexico, Australia and Canada. [8][9][10][11][12][13][14] Health warnings also have the potential to prevent smoking initiation among nonsmokers, including youth. 15 Smokers rate health warnings on cigarette packages as a prominent and credible source of information about the harms of tobacco use.…”
Section: Introductionmentioning
confidence: 99%